Carbon Dioxide and Nitrous Oxide Emissions Impacted by Bioenergy Sorghum Management. Issue 5 (25th September 2014) - Storlien, Joseph O.; Hons, Frank M.; Wight, Jason P.; Heilman, James L.
Abstract : Modern bioenergy feedstocks, such as bioenergy sorghum [ Sorghum bicolor (L.) Moench], are being developed to supply future cellulosic biofuel demands. How these cropping systems impact greenhouse gas (GHG) emission of CO2 and N2 O from the soil is unknown and field research is necessary to elucidate the effects of agronomic management practices on soil trace gas emissions. We studied the effects of N fertilization (0 vs. 280 kg urea‐N ha −1 ), residue management (0 vs. 50% of sorghum biomass returned), crop sequence (corn [ Zea mays L.]–sorghum vs. sorghum–sorghum), and their interactions on CO2 and N2 O emissions from bioenergy production scenarios on a Weswood (fine‐silty, mixed, superactive, thermic Udifluventic Haplustept) silty clay loam soil in central Texas. Gas fluxes were measured approximately weekly throughout the 2010 and 2011 growing season and at a reduced rate during the fallow season with a photoacoustic gas analyzer integrated with a static chamber. Overall, CO2 and N2 O fluxes were relatively higher than those observed by others in the United States despite drought conditions throughout much of 2010 and 2011. Highest emissions of both gases were observed during the growing season, often following a precipitation–irrigation event and shortly after N fertilization. Residue return increased cumulative CO2 emissions each year, probably due to increased heterotrophic microbial activity. Nitrogen addition significantly increased cumulative emissions of N2 O both years but only impacted cumulative CO2 emissions in 2011. While crop rotation impacted biomass yield, it had no significant effect on cumulative CO2 or N2 O emissions. Additional research is needed to identify the optimal N and residue application rates that provide high yields with minimal soil GHG emissions and aid in sustaining long‐term soil quality.